Electrospun carbon nano-felt derived from alkali lignin for cost-effective counter electrodes of dye-sensitized solar cells. Issue 14 (28th January 2016) - Ma, Xiaojing; Elbohy, Hytham; Sigdel, Sudhan; Lai, Chuilin; Qiao, Qiquan; Fong, Hao
Abstract : Electrospun lignin-derived carbon nano-felts (with or without surface-decoration of Pt nanoparticles) have been studied as cost-effective counter electrodes of DSSCs. Abstract : In this study, freestanding and mechanically flexible nano-felt consisting of electrospun carbon nanofibers (ECNFs) derived from alkali lignin with a BET specific surface area of ∼583 cm 2 g −1 and average pore size of ∼3.5 nm was prepared and then surface-deposited with Pt nanoparticles (Pt NPs). Both nano-felts of ECNFs and ECNFs–Pt were studied as cost-effective counter electrodes of dye-sensitized solar cells (DSSCs). The energy-dispersive X-ray spectroscopy (EDS) results showed that the amount of Pt NPs in ECNFs–Pt nano-felt was ∼9.9 wt%, and the scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray diffraction (XRD) results indicated that the Pt NPs with small sizes in the range of 2–20 nm were randomly distributed on the surface of ECNFs. The electrochemical impedance spectroscopy (EIS) tests revealed that the ECNFs-based counter electrode had low charge transfer resistance ( R ct = 1.94 Ω cm 2 ), and the R ct value was reduced to 1.2 Ω cm 2 upon surface-deposition of Pt NPs. The prototype DSSCs based on ECNFs and ECNFs–Pt counter electrodes exhibited comparable performances to the DSSC based on a conventional Pt counter electrode in terms of short circuit density ( J sc ), open circuit voltage ( V oc ), fill factor (FF), and energy conversion efficiency ( η ).